Huta Tomok Tourism Pier as Samosir Tourism Gate - Nurlisa Ginting; Yuda Juliandi (International Journal of Architecture and Urbanism, 2018)
Samosir is one of the famous tourist attraction for the beautiful view of nature of Lake Toba and some traditional cultural sites. Samosir began to start independent and has they have managing system for every area, and one of them is a tourist attraction. This area has the infrastructure that should be available very well, the most important thing in tourist attraction context in Samosir Island is the water crossing terminal because water transportation is the main part of tourist attractions life in Samosir Island. Tomok Village’s dock is one of the main doors that very busy with so many visits from the passenger. To provide a decent service, this dock is still far from expectations. Can be seen from the limit of the passengers this dock can afford, with the increasing intensity of passengers. However, this region needs to redevelopment using every single available potential. In the end, the dockyard should be attractive and give a great experience of Batak Toba culture. The designer will create the cultural experience through the display of the buildings. The designer hopes to facilitate passengers to cross the lake to Samosir island using Tomok village’s dockyard.